Linearization of Hue Value on The Surface of Thermochromic Liquid Crystal With Variation of Temperature - Risti Suryantari; Flaviana F (Department of Physics, Sebelas Maret University, 2015)
This research has observed a linear relation of hue value on the surface of a Thermochromic Liquid Crystal (TLC), with variation of temperature, based on statistic value of hue image. In this research we use ample of TLC with temperature range 250-300 C and 300-350 C. The original image in RGB format is converted to HSV (hue, saturation, value) and by taking hue without saturation and value, then the hue image is processed using Matlab2013a based on a mathematical morphology with opening and closing for the main process to get better images. The final image of each temperature variation can be distinguished based on the statistic value of each image. The value of max and mean hue increases by increasing temperature for each sample. Both samples tend to have the same linearization based on its mean value.